2020
DOI: 10.1093/jjco/hyaa042
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of the MET inhibitor tepotinib in Japanese patients with solid tumors

Abstract: Objectives Tepotinib (MSC2156119J) is an oral, potent and highly selective small molecule mesenchymal-epithelial transition factor (MET) inhibitor for which the recommended Phase II dose of 500 mg once daily has been defined, based on the first-in-man trial conducted in the USA and Europe. We carried out a multicenter Phase I trial with a classic `3 + 3' design to determine the recommended Phase II dose in Japanese patients with solid tumors (NCT01832506). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…In our case, tepotinib concentration in CSF was 30.6 ng/mL, which was enough to exceed the IC50. Moreover, Shitara and colleagues [10] conducted a phase I trial on Japanese patients, and observed an average steady‐state concentration of tepotinib in the plasma, ranging from 760.3 ng/mL to 1126.8 ng/mL. Thus, the concentration of tepotinib in the CSF exceeded the IC50.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, tepotinib concentration in CSF was 30.6 ng/mL, which was enough to exceed the IC50. Moreover, Shitara and colleagues [10] conducted a phase I trial on Japanese patients, and observed an average steady‐state concentration of tepotinib in the plasma, ranging from 760.3 ng/mL to 1126.8 ng/mL. Thus, the concentration of tepotinib in the CSF exceeded the IC50.…”
Section: Discussionmentioning
confidence: 99%
“…This dosing level is consistent with studies of tepotinib in other tumour types, and in Asian patients with HCC with MET overexpression. 24,28,30 Preliminary anti-tumour activity was observed in Phase 1b with tepotinib: two patients achieved PR and four patients achieved SD. Following results from Phase 1b, Phase 2 investigated the efficacy and safety of tepotinib dosed at 500 mg QD in patients with HCC tumours with MET overexpression who had previously been treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile observed in Phase 2 was consistent with Phase 1b and with other studies of tepotinib. 24,25,28,30 Treatment-related AEs were reported in 83.7% of patients overall and at Grade ≥3 in 28.6%. The most common Grade ≥3 treatment-related AEs were peripheral oedema and increased lipase, which are both known safety signals with tepotinib.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a single 500 mg dose of tepotinib was well tolerated by healthy volunteers; although 75% experienced TEAEs, most were mild and resolved rapidly. Tepotinib has also been found to be well tolerated in phase I/Ib and phase II clinical trials in patients with solid tumors, which have further characterized its side-effect profile [9,17,18,21,35,36]. Ongoing phase II trials in NSCLC and hepatocellular carcinoma will add further insight into the side-effect profile and efficacy of tepotinib [16-18, 20-22, 35].…”
Section: Discussionmentioning
confidence: 99%